A coarse-to-fine adaptive spatial–temporal graph convolution network with residuals for motor imagery decoding from the same limb - Zhu, Lei; Yuan, Jie; Huang, Aiai; Zhang, Jianhai (Biomedical signal processing and control, 2024)
•A novel coarse-to-fine classification approach is proposed to decode MI tasks of the same upper limb.•A adaptive spatial–temporal graph convolutional network with residuals approach is proposed to extract spatial–temporal features.•Various classification models are applied to different classification stages, and each model is specifically designed according to the feature differences among categories.•The proposed approach obtains better results than classical approaches. In the field of Brain Computer Interface (BCI) technology, Motor Imagery (MI) plays an important role as a paradigm. One of the primary focuses of this research area lies in exploring the MI of various upper limbs. Decoding MI signals from distinct joints within the same limb poses more intricate challenges in comparison to decoding MI signals originating from different upper limbs. In order to explore more efficient decoding methods, we propose a novel coarse-to-fine classification approach to investigate categorical decoding across three tasks, namely ‘rest’, ‘hand’, and ‘elbow’. This approach consists of two classification stages performed from coarse to fine. In the coarse classification stage, in order to capture the features of both resting state and the moving state in the temporal domain, the EEGNet network with temporal domain convolution is used to extract temporal domain features and classify the original samples into categories of ‘rest’ and ‘move’ (‘hand’, ‘elbow’). In the fine classification stage, the samples of ‘move’ category are segmented by time to form a graph sequence. Then, an adaptive spatial–temporal graph convolutional network with residuals is utilized to extract both temporal and spatial domains’ features from the graph sequence. The proposed algorithm has been validated experimentally on the MI-2 dataset and compared with contemporary methods. Its classification performance is quantified by the average accuracy which achieves a value of 72.21%. Extensive experimental results indicate that the novel coarse-to-fine classification approach is superior to the single classification approach.